The Chinese herb Styrax triggers pharmacokinetic herb-drug interactions via inhibiting intestinal CYP3A - Zhang, Feng; Zhang, Tiantian; Gong, Jiahao; Fang, Qinqin; Qi, Shenglan; Li, Mengting; Han, Yan; Liu, Wei; Ge, Guangbo (Frontiers in Pharmacology, 2022)
Human cytochrome P450 3A4 (hCYP3A4) is a predominant enzyme to trigger clinically relevant drug/herb-drug interactions (DDIs or HDIs). Although a number of herbal medicines have been found with strong anti-hCYP3A4 effects in vitro, the in vivo modulatory effects of herbal medicines on hCYP3A4 and their potential risks to trigger HDIs are rarely investigated. Herein, we demonstrate a case study to efficiently find the herbal medicine(s) with potent hCYP3A4 inhibition in vitro and to accurately assess the potential HDIs risk in vivo. Following screening over 100 herbal medicines, the Chinese herb Styrax was found with the most potent hCYP3A4 inhibition in HLMs. In vitro assays demonstrated that Styrax could potently inhibit mammalian CYP3A in liver and intestinal microsomes from both humans and rats. In vivo pharmacokinetic assays showed that Styrax (i.g., 100 mg/kg) significantly elevated the plasma exposure of two CYP3A-substrate drugs (midazolam and felodipine) when midazolam or felodipine was administered orally. By contrast, the plasma exposure of either midazolam or felodipine was hardly affected by Styrax (i.g.) when the victim drug was administered intravenously. Further investigations demonstrated that seven pentacyclic triterpenoid acids (PTAs) in Styrax were key substances responsible for CYP3A inhibition, while these PTAs could be exposed to intestinal tract at relatively high exposure levels but their exposure levels in rat plasma and liver were extremely low. These findings well explained why Styrax (i.g.) could elevate the plasma exposure of victim drugs only when these agents were orally administrated. Collectively, our findings demonstrate that Styrax can modulate the pharmacokinetic behavior of CYP3A-substrate drugs via inhibiting intestinal CYP3A, which is very helpful for the clinical pharmacologists to better assess the HDIs triggered by Styrax or Styrax-related herbal products.